The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0181942
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel antigen candidates for a tuberculosis vaccine in the adult zebrafish (Danio rerio)

Abstract: Tuberculosis (TB) remains a major global health challenge and the development of a better vaccine takes center stage in fighting the disease. For this purpose, animal models that are capable of replicating the course of the disease and are suitable for the early-stage screening of vaccine candidates are needed. A Mycobacterium marinum infection in adult zebrafish resembles human TB. Here, we present a pre-clinical screen for a DNA-based tuberculosis vaccine in the adult zebrafish using an M. marinum infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 81 publications
(127 reference statements)
0
41
0
1
Order By: Relevance
“…, and is widely used as an animal model in vaccine research owing to its advantages of small size, easy reproduction, and low cost [36]. A er infection by M. marinum, both adult zebrafish and larvae can form granulomas that are very similar to those observed in humans, and the innate and adaptive immune responses elicited against mycobacteria are composed of the same primary components found in humans [37][38][39]. In addition, the transparent characteristic of zebrafish larvae is also suitable for fluorescence imaging.…”
Section: Goats Goats Can Be Naturally Infected Bymentioning
confidence: 99%
See 1 more Smart Citation
“…, and is widely used as an animal model in vaccine research owing to its advantages of small size, easy reproduction, and low cost [36]. A er infection by M. marinum, both adult zebrafish and larvae can form granulomas that are very similar to those observed in humans, and the innate and adaptive immune responses elicited against mycobacteria are composed of the same primary components found in humans [37][38][39]. In addition, the transparent characteristic of zebrafish larvae is also suitable for fluorescence imaging.…”
Section: Goats Goats Can Be Naturally Infected Bymentioning
confidence: 99%
“…Although zebrafishes are very different to humans in genetic terms, the above characteristics of this model have helped to bridge the gap between fish and humans. Data obtained from zebrafish studies have already shown that BCG vaccination, as well as DNA vaccination, can protect adult zebrafish from M. marinum infection by reducing both the mortality and bacterial counts in a manner dependent on the adaptive immune response and enhanced production of IFN-γ [38,113]. In addition to its use for the preclinical screening of vaccines, the zebrafish model has been used in clarifying the mechanisms underlying granuloma formation [114].…”
Section: Goats Goats Can Be Naturally Infected Bymentioning
confidence: 99%
“…As previously, reported vaccine candidate (Myllymaki et al, 2017), the role of PE31 in host interactions and pathogenesis of M. tuberculosis has remained to be understood. M. tuberculosis survival within macrophages is necessitates effective neutralization of hostile environments such as acidification, oxygen radicals, and RNIs (Cossu et al, 2012;Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the PE31 interact with PPE18, and able to form a heterodimeric complex with TLR 2 (Mukhopadhyay and Balaji, 2011). While another report suggested that PE31 with PE51 are protective antigens (Myllymaki et al, 2017). However, the exact role of PE31 in pathogenicity, host-pathogen interaction and underlying mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…An infection by Mycobacterium marinum in adult zebrafish resembles that of human tuberculosis, as demonstrated by Myllymäki et al [62]. Those authors proved that the M. marinum infection model in adult zebrafish was suitable for preclinical screening of tuberculosis immune's responses and vaccines.…”
Section: Animals and Human Vaccinesmentioning
confidence: 89%